Comparison of degradation kinetics of tannery wastewater treatment using a nonlinear model by salt-tolerant Nitrosomonas sp. and Nitrobacter sp. (May 2022) - Dang, Bao-Trong; Tran, Duyen P.H.; Nguyen, Ngoc-Kim-Qui; Cao, Huong T.N.; Tomoaki, Itayama; Huynh, Ky-Phuong-Ha; Pham, Tan-Thi; Varjani, Sunita; Hao Ngo, Huu; Wang, Ya-Fen; You, Sheng-Jie; Bui, Xuan-Thanh
Graphical abstract: Highlights: Nitrification was successfully activated by salt tolerant bacteria (STB). STB enhanced COD and TKN removal by 11% and 23%. The produced NO2 – -N and NO3 – -N was co-fitted with the logistic function. Free ammonia and high C/N ratio reduced the nitrite oxidation when using STB. Abstract: Conventional biological treatment has been reported to be ineffective for pollutant removal in tannery wastewater due to high salinity.﻿ ﻿To overcome it, this work used salt-tolerant bacteria (STB) isolated from a membrane bioreactor to evaluate the organic and nutrient removal through a series of batch experiments. Compared with the control, the STB reactor enhanced the reduction of persistent organics by 11% based on the double exponential decay model. Besides, the removal of NH4 + -N is 26% higher, satisfying the first-order decay model. The nitrification was inhibited entirely in control during 48 h, whilst the assimilation process involved 55% of total nitrogen removal. In the STB reactor, nitrification occurred after 12 h, resulting in significantly increased NO2 – -N and NO3 – -N concentrations according to the logistic function. Although nitrification was successfully activated, C/N ratios and free ammonia were identified as limiting factors for STB activity, requiring mitigation strategies in further studies.